Prostituição feminina: uma análise a partir das categorias trabalho e gênero - Santana, Maísa Aguiar (2013)
This research has as an object of study female prostitution from the categories labor and gender. For both, it was discussed that the activity in the light of Marxist perspective focusing on productive and unproductive labor categories, seizing prostitution as a service. Moreover, the approach is contemporary transformations in the world of work, especially women´s work and its relation to prostitution. Was used as a method, materialism historical-dialectical, taking reality as a starting point. This is theoretical research, Qualitative and bibliographical and documentary character nature. It was found that the work accessed, no research addressing prostitution were found from the categories productive and unproductive labor in Marx. Thus, the authors claim that this activity is a work, based on the idea of prostitution as a means of survival. The research here presented, in addition to the determination of prostitution as an alternative income, points out that such activity is not a job, from the standpoint of social theory of Marx, considered as a service. Notwithstanding the various relations between prostitutes and owners brothels, the prostitute can not be considered a productive worker, since it does not generate added value, fundamental mediator for the characterization of productive work in production mode capitalist. Furthermore, we visualized prostitution as an activity pervaded by relations unequal gender, being mostly carried out by women and the nature of services provided, a service of a sexual nature.